Land law reform in Kenya: Devolution, veto players, and the limits of an institutional fix. Issue 471 (14th March 2019) - Boone, Catherine; Dyzenhaus, Alex; Manji, Ambreena; Gateri, Catherine W; Ouma, Seth; Owino, James Kabugu; Gargule, Achiba; Klopp, Jacqueline M
Abstract: Much of the promise of the good governance agenda in African countries since the 1990s rested on reforms aimed at 'getting the institutions right', sometimes by creating regulatory agencies that would be above the fray of partisan politics. Such 'institutional fix' strategies are often frustrated because the new institutions themselves are embedded in existing state structures and power relations. The article argues that implementing Kenya's land law reforms in the 2012–2016 period illustrates this dynamic. In Kenya, democratic structures and the 2010 constitutional devolution of power to county governments created a complex institutional playing field, the contours of which shaped the course of reform. Diverse actors in both administrative and representative institutions of the state, at both the national and county levels, were empowered as 'veto players' whose consent and cooperation was required to realize the reform mandate. An analysis of land administration reform in eight Kenyan counties shows how veto players were able to slow or curtail the implementation of the new land laws. Theories of African politics that focus on informal power networks and state incapacity may miss the extent to which formal state structures and the actors empowered within them can shape the course of reform, either by thwarting the reformist thrust of new laws or by trying to harness their reformist potential.